Interaction of banking and real sectors of economy: estimation of effects on the basis of modeling (Journal of Economic Research & Business Administration, 2017)
The present article explores the actual problems of interaction between the banking and real sectors of the economy, limiting the effective and harmonious cooperation of their subjects in the context of the need to ensure sustainable macroeconomic effects and the cyclical nature of the development of the modern economy. Using the methods of economic and mathematical modeling and the use of a wide range of panels data for a number of countries, the composition of which was aggregated into groups depending on the degree of development over the last 30 years. Conclusions were obtained regarding the impact of the results of interaction between the banking and real sectors on the rates of economic growth, the interdependence of investment and credit policy and the state of the developing economy. It is concluded that for such countries as Kazakhstan and Russia, institutional changes at the micro-, meso-, and macro- levels have a significant impact on the quality of interaction between the subjects of the banking and real sectors of the economy. The system approach used in the work made it possible to identify promising areas for the development of interaction between banking institutions and enterprises in the real sector of the economy, with an emphasis on activating innovation in both sectors and improvinginstitutions that together form the basis for coordinated and effective interaction of the banking andreal sector entities focused on achieving both individual goals for banks and enterprises (micro-effects),and effects in the region cial and country-wide (effects on the meso- and macro- levels) – for ensureprogressive socio-economic development of the country.